The Application of Imaging and Molecular Markers in Cancer Diagnosis and Treatment - Wang, Teng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer is one of the leading causes of death worldwide, and its diagnosis and treatment face many challenges. In recent years, the combination of imaging techniques and molecular markers has made remarkable progress in cancer diagnosis and treatment. Imaging techniques such as CT, MRI and PET-CT can provide anatomical and functional information of tumors, while molecular markers such as EGFR and HER2 play a key role in tumor diagnosis, prognosis and treatment. However, how to effectively combine these technologies to achieve more accurate diagnosis and treatment is still a gap in research. This paper reviews the combined application of imaging technology and molecular markers in cancer diagnosis, therapeutic response monitoring and individualized therapy, analyzes the synergistic effect of multimodal imaging technology and molecular markers, and finds that it has significant advantages in early detection and individualized treatment planning. Combining imaging and molecular marker information can improve the accuracy of cancer diagnosis and guide targeted therapies. The combination of such technologies provides a new reference for precision cancer medicine in the future, but further research is still needed in the aspects of marker sensitivity and image analysis automation. In the future, the combination of new technologies such as artificial intelligence is expected to promote the development of more accurate and efficient cancer diagnosis and treatment.